Integrity hour and the mental health continuum - Vogt, Lisa; Sawatzky, Breanna; Villafranca, Pamela (Canadian Perspectives on Academic Integrity, 2022)
Supporting academic integrity across the institution is an involved process that includes integrating proactive education, designing effective learning spaces, identifying potential academic integrity breaches, and finding resolutions to support student learning. Through published literature as well as anecdotal experiences, we know that upholding the spectrum of academic integrity can take a toll on everyone – including students, instructors, administrators, and support staff. Rapid transitions and isolation brought on by responses to COVID-19 have only intensified this challenge. Using the Integrity Hour model developed by Dr. Sarah Elaine Eaton at the University of Calgary, RRC Polytech has established a community of practice to support staff and grow the institutional culture of academic integrity. In this session, participants will learn more about the Integrity Hour community at RRC Polytech and how the mental health continuum resource has been used to support group discussion. This session will include a demonstration of the Integrity Hour process with an invitation to participate in a circle discussion.